A synthesis method and application of sodium vanadium pyrophosphate / carbon composite material

Through the synthesis method of sodium vanadium pyrophosphate/carbon composite material, the problems of high cyclic attenuation rate and low conductivity of the material in sodium ion batteries are solved, and better electrochemical cycling stability and conductivity are achieved, which is suitable for the positive electrode materials of sodium ion batteries.

CN118929617BActive Publication Date: 2025-03-18SHANDONG HAIHUA GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411418577.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-18
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The cycling attenuation rate of vanadium pyrophosphate in sodium ion batteries is high and the conductivity is low, resulting in unstable electrochemical performance.

Method used

The synthesis method of vanadium pyrophosphate/carbon composite material is adopted. The sodium salt, vanadium-containing compound, ammonium phosphate and citric acid are heated and stirred in deionized water to form a sol. After drying and ball milling, it is ultrasonic dispersed and hydrothermal reaction with graphene oxide (GO) to form a NaVP2O7 precursor/rGO suspension, and finally calcined in an inert atmosphere to obtain the sodium vanadium pyrophosphate/carbon composite material.

Benefits of technology

It significantly reduces the cycle attenuation rate of sodium vanadium pyrophosphate/carbon composite material, improves its electrochemical cycle stability and conductivity, and is suitable for sodium ion battery positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929617B_ABST
    Figure CN118929617B_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of sodium vanadium pyrophosphate / carbon composite material and its application, belonging to the technical field of sodium ion battery electrode materials. The synthesis method comprises adding sodium salt, vanadium-containing compound, ammonium phosphate and citric acid into deionized water, heating, stirring, drying and ball milling to obtain NaVP 2 O 7 Precursor material: adding the precursor material and GO into deionized water for hydrothermal reaction to obtain NaVP 2 O 7 Precursor / rGO suspension, then NaVP 2 O 7 The precursor / rGO suspension was filtered, washed, dried, and calcined in an inert atmosphere to obtain sodium vanadium pyrophosphate / carbon composite material. The composite material has a stable intrinsic structure, high redox potential and high temperature resistance; it was applied to sodium ion batteries, and after 1000 cycles at a current density of 1C, the charge-discharge specific capacity can be maintained at 85.39mAhg ‑1 , the cycle attenuation rate is as low as 0.01%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery electrode materials, and in particular to a synthesis method of a sodium vanadium pyrophosphate / carbon composite material and application thereof. Background Art

[0002] Green renewable energy is an ideal energy source. Its intermittent characteristics require the configuration of energy storage equipment. Electrochemical energy storage equipment has attracted widespread attention due to its advantages such as high electricity conversion rate and controllable scale.

[0003] Sodium-ion batteries have abundant sodium reserves and excellent high and low temperature performance, which has triggered in-depth research by researchers. Polyanion materials are one of the main technical routes for positive electrode materials of sodium-ion batteries. According to the type of anions, they are classified into: phosphates, pyrophosphates, fluorophosphates, sulfates, silicates and other types of materials. This type of material has a three-dimensional framework structure composed of strong covalent bonds and has high structural stability. Vanadium-based polyanion materials have abundant (V 2 + 、V 3+ 、V 4+ 、V 5+ ) valence state, the redox potential is relatively high. Among them, the pyrophosphate NaVP2O7 has an obvious redox potential at 3.9V, and the theoretical specific capacity is about 108.1mAhg -1 , with a high theoretical energy density of 421Whkg -1 In addition, pyrophosphate NaVP2O7 has good stability under high temperature and high pressure conditions, and has good application prospects in special application fields. However, the large framework structure of the pyrophosphate group ensures the thermal stability of the material, but also causes problems such as low conductivity and fast cycle decay. Researchers continue to improve it to optimize the electrochemical performance of the material. Summary of the invention

[0004] The method of the present invention aims to provide a synthesis method of a sodium vanadium pyrophosphate / carbon composite material and its application. The prepared sodium vanadium pyrophosphate / carbon composite material has a low cycle attenuation rate and good cycle stability, and is suitable for a positive electrode material of a sodium ion battery.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In one aspect, the present invention provides a method for synthesizing a sodium vanadium pyrophosphate / carbon composite material, comprising the following steps:

[0007] (1) adding sodium salt, vanadium-containing compound, ammonium phosphate and citric acid into deionized water, heating and stirring to form a sol, drying the sol to obtain a dry gel, and ball-milling the dry gel to obtain a NaVP2O7 precursor material;

[0008] (2) adding NaVP2O7 precursor material and GO into deionized water, and ultrasonically dispersing them to form a mixed solution; subjecting the mixed solution to a hydrothermal reaction to obtain a NaVP2O7 precursor / rGO suspension, wherein GO is graphene oxide;

[0009] (3) The NaVP2O7 precursor / rGO suspension is filtered, washed, and dried to obtain a powder precipitate, which is then calcined in an inert atmosphere to obtain a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO).

[0010] Furthermore, in the step (1), the molar ratio of sodium salt, vanadium-containing compound, ammonium phosphate and citric acid is 10-13 mol:10 mol:20 mol:3 mol; the sodium salt is one of Na2CO3, NaCl and Na2C2O4; the vanadium-containing compound is NH4VO3 or V2O5; the ammonium phosphate is NH4H2PO4 or (NH4)2HPO4; the ball-to-material ratio is 1:10-20, the rotation speed is 500-700 r / min, and the grinding time is 3-8 h.

[0011] Furthermore, in the step (2), the mass ratio of NaVP2O7 precursor material to GO is 10-30:1; the hydrothermal reaction temperature is 150-170°C; and the heating time is 5-10h.

[0012] Furthermore, in the step (3), the calcination temperature is 600°C to 800°C, and the calcination time is 8 to 10 hours.

[0013] On the other hand, the present invention also provides a method for using the sodium vanadium pyrophosphate / carbon composite material prepared by the above method as a positive electrode material for a sodium ion battery.

[0014] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0015] The pyrophosphate prepared by the traditional preparation method has poor conductivity, and the resistance of electrons and ions during the shuttling process is relatively large; the technical solution of the present invention first adds sodium salt, vanadium-containing compound, ammonium phosphate and citric acid into deionized water, heats and stirs to carry out liquid phase reaction, so that the three carboxylic acid groups on the citric acid molecules are combined with vanadium metal ions to different degrees to form coordination polymers to form molecular chains, and the molecular chains are cross-linked with each other to gradually form a sol with a network framework structure; then the solvent molecules sealed in the network framework are evaporated through drying to form a network-like dry gel; the dry gel is ball-milled to break the dry gel into a network-like thin sheet material, and the particle size of the thin sheet material is controlled to 500-600nm by controlling the ball milling speed and duration; compared with the traditional pyrophosphate, the network-like thin sheet material has a smaller particle size and a larger surface area, can shorten the ion diffusion particle size, expose more active sites, reduce the material resistance, and is conducive to the release of the specific capacity of the NaVP2O7 material.

[0016] The technical solution of the present invention adds pulverized NaVP2O7 precursor material and GO into deionized water, and under the action of ultrasound, the NaVP2O7 precursor material is loaded on GO to form a NaVP2O7 precursor / GO suspension; irregular flaky materials of about 500-600nm are loaded on the wrinkled GO, which not only avoids the sintering of NaVP2O7 during the calcination process, but also better maintains the structural stability during the cycle process; and then the oxygen-containing functional groups on GO are reduced through a hydrothermal reaction to improve the conductivity of the material, and finally a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) with good electrochemical cycle stability and conductivity is formed.

[0017] The technical solution of the present invention controls the calcination temperature and duration of the powder precipitate in an inert atmosphere to cause phosphate to undergo a polymerization reaction to form pyrophosphate. The pyrophosphate has a more stable intrinsic structure, a higher redox potential and better high temperature resistance, and can significantly improve the high temperature resistance of the product, providing a new synthesis path for the preparation of high temperature and high pressure electrode materials.

[0018] The technical solution of the present invention has a good effect on improving the conductivity of NaVP2O7 materials. The sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) is applied to sodium ion batteries to show relatively excellent electrochemical performance. The capacity is maintained at 85.39 mAhg after 1000 cycles under 1C conditions. -1 , the cycle attenuation rate is as low as 0.01%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a morphology picture of the NaVP2O7 precursor material obtained in Example 1 observed by a scanning electron microscope at 7210 times;

[0020] Figure 2This is a morphology picture of the sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) obtained in Example 1 under an electron microscope with a magnification of 9350 times;

[0021] Figure 3 This is a scanning electron microscope image of the NaVP2O7 material obtained in the comparative example after calcination, observed at 10480 times;

[0022] Figure 4 This is the XRD diffraction pattern of the sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) obtained in Example 1;

[0023] Figure 5 This is a graph showing the cycling performance of the sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) obtained in Example 1 as a positive electrode material in a sodium ion battery at a current density of 1C. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the embodiments. The drawings and embodiments of the specification are only used to explain the present invention and do not constitute an improper limitation of the present invention. Example 1

[0025] (1) 0.13 mol Na2CO3, 0.1 mol V2O5, 0.2 mol NH4H2PO4, and 0.03 mol citric acid were added to 1 L of deionized water and stirred at 80 °C for 1 h to obtain a sol, which was placed in an oven for drying to obtain a dry gel. The dry gel and grinding balls were added to a grinding jar at a weight ratio of 1:10, and ground at 700 r / min for 3 h to obtain a NaVP2O7 precursor material;

[0026] (2) Will 500 mg of NaVP2O7 precursor material was added to deionized water for ultrasonic dispersion to form a solution, and 20 mg of GO was added during the ultrasonic process to form a mixed solution; the mixed solution was transferred to a reactor and heated at 160° C. for 10 h to obtain a NaVP2O7 precursor / rGO suspension;

[0027] (3) The NaVP2O7 precursor / rGO suspension was filtered, washed, and dried to obtain a powder precipitate, which was then calcined at 800°C in an Ar atmosphere for 10 h to obtain a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO).

[0028] The NaVP2O7 precursor material obtained in Example 1 was characterized by a scanning electron microscope (SEM). The results of the SEM test at 7210 times were as follows: Figure 1As shown. If the material is formed directly by stirring the solution, it is easy to form a large block of material. The technical solution of the present invention obtains a 500-600nm network-like thin sheet material through the steps of forming a sol, a dry gel, and ball milling and pulverization, which can shorten the ion diffusion path, expose more active sites, reduce the material resistance, and is conducive to the release of the specific capacity of the NaVP2O7 material. After the ball-milled material is directly calcined, the material morphology and structure are as follows Figure 3 As shown, the material will be sintered. The NaVP2O7 / rGO composite material finally obtained in Example 1 was observed by scanning electron microscopy at a magnification of 9350. Figure 2 As shown in the figure, the pulverized NaVP2O7 precursor material and GO were hydrothermally reduced and subsequently calcined to finally form a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO) with a high degree of compositeness. The irregular flake material of about 500~600nm is loaded on the wrinkled rGO, which not only avoids the sintering of NaVP2O7 during the calcination process, but also keeps the irregular flake structure evenly dispersed on rGO. The formation of this structure can not only effectively improve the electrochemical performance of the material, but also better maintain the structural stability during the cycle process. Figure 5 As shown in Figure 2, the material maintained a capacity of 85.39 mAh g after 1000 cycles at 1C. -1 The cycle attenuation rate is as low as 0.01%. The XRD diffraction test was carried out on it, and the results are as follows Figure 4 The shown demonstrates the efficient synthesis of the material. Example 2

[0029] (1) 0.1 mol NaCl, 0.1 mol V2O5, 0.2 mol (NH4)2HPO4, and 0.03 mol citric acid were added to 1 L of deionized water and stirred at 80 °C for 1 h to obtain a sol, which was placed in an oven for drying to obtain a dry gel. The dry gel and grinding balls were added to a grinding jar at a weight ratio of 1:15, and ground at 600 r / min for 5 h to obtain a NaVP2O7 precursor material;

[0030] (2) 500 mg of NaVP2O7 precursor material was added to deionized water and ultrasonically dispersed to form a solution. During the ultrasonic process, 30 mg of GO was added to form a mixed solution. The mixed solution was transferred to a reactor and heated at 170 °C for 5 h to obtain a NaVP2O7 precursor / rGO suspension.

[0031] (3) The NaVP2O7 precursor / rGO suspension was filtered, washed, and dried to obtain a powder precipitate, which was then calcined at 700°C in an Ar atmosphere for 10 h to obtain a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO). Example 3

[0032] (1) 0.11 mol Na2C2O4, 0.1 mol NH4VO3, 0.2 mol (NH4)2HPO4, and 0.03 mol citric acid were added to 1 L of deionized water and stirred at 80 °C for 1 h to obtain a sol, which was placed in an oven for drying to obtain a dry gel. The dry gel and grinding balls were added to a grinding jar at a weight ratio of 1:20, and ground at 500 r / min for 8 h to obtain a NaVP2O7 precursor material;

[0033] (2) 500 mg of NaVP2O7 precursor material was added to deionized water for ultrasonic dispersion to form a solution, and 10 mg of GO was added during the ultrasonic process to form a mixed solution; the mixed solution was transferred to a reactor and heated at 160 °C for 8 h to obtain a NaVP2O7 precursor / rGO suspension;

[0034] (3) The NaVP2O7 precursor / rGO suspension was filtered, washed, and dried to obtain a powder precipitate, which was then calcined at 800°C for 3 h in an Ar atmosphere to obtain a sodium vanadium pyrophosphate / carbon composite material (NaVP2O7 / rGO). Comparative Example

[0035] (1) 0.13 mol Na2CO3, 0.1 mol V2O5, 0.2 mol NH4H2PO4, and 0.03 mol citric acid were added to 1 L of deionized water and stirred at 80 °C for 1 h to obtain a sol, which was then placed in an oven for drying to obtain a dry gel. The dry gel and grinding balls were added to a grinding jar at a weight ratio of 1:10, and ground at 700 r / min for 3 h to obtain a NaVP2O7 precursor material;

[0036] (2) The NaVP2O7 precursor material was calcined at 800°C in an Ar atmosphere for 10 h to obtain the NaVP2O7 material.

[0037]

[0038] The materials prepared in the examples and comparative examples were used as positive electrodes in sodium ion batteries. From the data in Table 1, it can be seen that the electrochemical performance of the material obtained in Example 1 is the best, proving that the conditions used in Example 1 are the best combination of conditions. In the comparative example, the material was not composited with wrinkled rGO, and the cycle stability was poor, failing to complete 1000 cycles. It is further proved that the irregular fragments of NaVP2O7 are conducive to the release of material capacity, and the composite of rGO and the irregular fragments of NaVP2O7 is conducive to maintaining structural stability and improving cycle stability.

Claims

1. A method for synthesizing a sodium vanadium pyrophosphate / carbon composite material, characterized in that: The steps include: (1) adding sodium salt, vanadium-containing compound, ammonium phosphate and citric acid into deionized water, heating and stirring to obtain a sol, drying the sol to obtain a dry gel, and ball-milling the dry gel to obtain a NaVP2O7 precursor material; (2) adding NaVP2O7 precursor material and GO into deionized water, and ultrasonically dispersing them to form a mixed solution; subjecting the mixed solution to a hydrothermal reaction to obtain a NaVP2O7 precursor / rGO suspension; (3) After filtering, washing and drying the NaVP2O7 precursor / rGO suspension, a powder precipitate is obtained, and the powder precipitate is calcined in an inert atmosphere to obtain a sodium vanadium pyrophosphate / carbon composite material; In the step (1), the sodium salt is one of Na2CO3, NaCl, and Na2C2O4; the vanadium-containing compound is NH4VO3 or V2O5; the ammonium phosphate is NH4H2PO4 or (NH4)2HPO4; the molar ratio of the sodium salt, the vanadium-containing compound, the ammonium phosphate, and the citric acid is 10-13 mol:10 mol:20 mol:3 mol; the ball-to-material ratio is 1:10-20, the rotation speed is 500-700 r / min, and the ball milling time is 3-8 h.

2. The method for synthesizing the sodium vanadium pyrophosphate / carbon composite material according to claim 1, characterized in that: In the step (2), the mass ratio of NaVP2O7 precursor material to GO is 10-30:1; the hydrothermal reaction temperature is 150-170°C; and the heating time is 5-10h.

3. The method for synthesizing the sodium vanadium pyrophosphate / carbon composite material according to claim 1, characterized in that: In the step (3), the calcination temperature is 600°C to 800°C and the calcination time is 8 to 10 hours.

4. An application of a sodium vanadium pyrophosphate / carbon composite material prepared by the synthesis method of the sodium vanadium pyrophosphate / carbon composite material according to any one of claims 1 to 3, characterized in that: The sodium vanadium pyrophosphate / carbon composite material is used as a positive electrode material for a sodium ion battery.

Citation Information

Patent Citations

  • Sodium vanadium pyrophosphate / carbon composite positive electrode material, and preparation and application thereof

    CN107017398A

  • Heteroatom-doped graphene-based sodium vanadium phosphate composite nanometer material of sodium ion positive electrode material

    CN109616651A